PS03 Systematic Review and Meta-Analysis of School-Based Interventions to Reduce Body Mass Index. (17th September 2012) - Lavelle, HV; Pell, JP; Mackay, DF
Abstract : Background: Childhood obesity predisposes to adult obesity and increases the risk of many diseases. Schools provide a vehicle to deliver public health interventions to all children. Methods: Medline and Embase were used to undertake a systematic review of published studies on school-based interventions aimed at reducing body mass index (BMI) of children ≤ 18 years. Preferred reporting items for systematic review and meta-analyses guidelines were followed, and eligible studies subjected to a random effects meta-analysis. Results: Between 1991 and 2010, 43 published studies provided 60 measurements of effect. The pooled effect was a 0.17 (95% CI: 0.08, 0.26, P <0.001) reduction in BMI. Heterogeneity was high ( I 2 =93.4%) but there was no significant small study bias (Egger's test, P =0.422) nor significant variation by length of follow-iup. The intervention comprised physical activity only in 11 (26%) studies, education only in three (7%), and combinations of these and improved nutrition in the remaining 29 (67%). On stratified analysis, physical activity used in isolation (-0.13, 95% CI: -0.22, -0.04, P =0.001) or combined with improved nutrition (-0.17, 95% CI: -0.29, -0.06, P <0.001) was associated with significant improvements in BMI. Interventions targeted at overweight/obese children reduced their BMI by 0.35 (95% CI: 0.12, 0.58, P =0.003). Those delivered to all children reduced it by 0.16 (95% CI: 0.06, 0.25, P =0.002). Conclusion: There is growing evidence that school-based interventions that contain a physical activity component may be effective in helping to reduce BMI in children.